Peningkatan Kesedaran Menabung Generasi Muda pada Bank Syariah di Kota Ternate - Muhammad Kamal; Suwito Suwito; Daud Hasim (Universitas Kristen Indonesia Toraja, 2024)
This socialization activity aims to foster and increase the interest and enthusiasm of the younger generation, especially students at Ulul Al Baab Junior High School and Madrasah Aliya Ulul Al Baab. In addition, to socialize institutions, goods and services products and sharia-based practices in business. This is intended to revive sharia practices as a new trend in the field of muamalah for the easy generation amid the strong dynamics of the economy with the conventional system. The lecture and dialog method of PKM took place for two months in Kalumata Village, South Ternate City, involving 48 students from Ulul Al Baab Junior High School and Madrasah Aliyah. Students were able to understand that Islamic banks operate based on Islamic principles, which prohibit usury and apply a profit-sharing system that is more transparent and fair.